Key determinants of Japanese commercial banks performance - Nasserinia, Ali; Syed Mohamed, Mohamed Ariff; Cheng, Fan Fah (Universiti Putra Malaysia Press, 2014)
This paper reports how six bank-specific characteristics and several market and macroeconomic factors influence Japan's commercial bank performance in the recent years that cover global crises. The results suggest that net interest margin is an important performance variable. It is negatively correlated with credit risk, capital adequacy, while liquidity risk, asset quality, management efficiency have positive influences. The effects of income diversification and size are positive though not significant; so, is bank concentration positive for performance. GDP growth and money supply have negative and significant relationships on performance although their effects are marginal compared with bank-specific variables. The global crisis did have significant effect. To take into account profit persistence, GMM technique was applied and it produced moderate support for earnings persistence and there is good deal of competition. These are findings on Japanese banking.